Optimization grid scheduling with priority base and bees algorithm - Ahmed, Mohammed Shihab (2014)
Grid computing depends upon sharing large-scales in a network that is widely connected within itself such as the Internet. Therefore, many grid computing researchers and scholars have focused on task scheduling, which is considered one of the NP-Complete issues. The main aim of this current research to propose an optimization of the initial scheduler for grid computing using the bees algorithm. Modern algorithms informed this research. The suggested procedure means that a newly developed algorithm can implement the schedule grid task while accounting for priorities and deadlines to decrease the completion time required for the tasks. The average waiting time of the grid environment can be minimized, and this minimization, in turn, creates an increase in the throughput of the environment.